Katharina Lescailje’s Ariadne and Public Femininity: Playbooks as a Source for Scholarship on Early Modern Women - van Elk, Martine (Early Modern Low Countries, 2025)
Combining literary analysis with book history, this short essay examines how representations of women within a play may be complicated by considering the context of individual printed versions. Ariadne, by Katharina Lescailje, offers a translation of Thomas Corneille’s tragedy, with its complicated female protagonist, for the Dutch stage. In the 1693 single edition and the 1731 complete edition of Lescailje’s work, this ambivalent representation of femininity is accompanied by title pages, a frontispiece, and a dedicatory poem that present Ariadne as eroticised and victimised, conflating her with Lescailje herself. In addition, Lescailje appears on title pages as translator, author, and stationer. All of these representations together show how printed versions of plays can add to the depiction of women in drama to display a variety of female roles for the reader to contemplate and explore.